The Potential of Nanocellulose Filter Paper (Neolamarckia Cadamba) For the Removal of Dyes from Textile Effluents - Azlan, Nur Nafika; A. Hamid, Hazren (Progress in Engineering Application and Technology, 2023)
Cellulose Nanofibers (CNFs), in particular, has drawn considerable attention to the developments made in nanotechnology because of its unique properties. In this study, Neolamarckia Cadamba was used as a raw material in the manufacture of nanocellulose filter paper for the removal of dyes from textile wastewater. Therefore, the goal of this study is to investigate the effectiveness of the filter paper made from renewable forest resources through cross-flow filtration system in terms of the dosages of 60:40 and 70:30. Reactive dyes were thought to be the most problematic chemical in textile effluent due to their high-water solubility, stability, and persistence in nature. Normalized flux, colour removal, water quality parameters, and membrane surface properties were used to analyze membrane fouling behaviour. The results showed that colour removal was 91.21%, and the water quality parameters achieved were within the allowed wastewater discharge limit. The goal of this project was to standardize wastewater treatment for the composite textile industry by using filter paper made of cellulose nanofibers (CNFs) as a membrane to remove dyes from wastewater. Thus, this study can verify the effectiveness of Neolamarckia Cadamba as raw source for filter paper.